Relationships Between Generated Musical Structure, Performers' Physiological Arousal and Listener Perceptions in Solo Piano Improvisation. Issue 4 (1st October 2016) - Dean, Roger T.; Bailes, Freya
Abstract : What musical structures do improvisers produce, and how do these relate to their physiological arousal while performing and to listener perceptions? Nine professional improvisers performed both structured and free improvisations. We hypothesized that increases in performers' arousal and attention during structural transitions would be reflected by changes in skin conductance. Consistent with the hypothesis, skin conductance changed particularly around transitions. Improvisers then listened to their improvisations, continuously rating musical change. Fourteen non-musicians also rated change, and separately rated perceptions of affect. Their perceptions related to structural parameters, though these were less influenced by musical features than those of the performers.